Effects of Different Dual-Modified Jujube Juicing Residue Dietary Fibers on the Properties of Egg Protein Gels Induced by Alkalinity and Heat - Xinyu Zheng; Ling Dang; Yichan Zhang; Xinyu Liu; Hui Wang; Yajun Zheng; Xinling Song; Zhihui Wei; Jiayao Zhang; Xiaoyang Guo (Gels)
Egg protein gels have relatively poor water-holding capacity, hardness, and freeze–thaw properties. Jujube juicing residue dietary fiber (JJRDF) is available, but it is rarely used in the food industry because of its poor hydration properties. Versions of JJRDF modified via cellulase and xylanase hydrolysis separately coupled with carboxymethylation (JJRDF-CXHC), phosphate crosslinking (JJRDF-CXHPC), and acetylation (JJRDF-CXHA) were prepared, and their effects on heat-induced and alkaline-induced egg protein gels (HA-EPGs) were studied. Smaller particle sizes and higher solubility, viscosity, expansion volume, and ability to retain water were observed in JJRDF-CXHC, JJRDF-CXHPC, and JJRDF-CXHA compared to JJRDF (p < 0.05). JJRDF-CXHC showed the highest viscosity (18.46 cP) and expansion volume (10.40 mL/g). Higher random coil and β-sheet contents resulted in an increase in pH, adhesiveness, hardness, and chewiness, and a decrease in the water-losing rate in freeze–thaw cycles, and gastric digestion was observed in the HA-EPGs as a consequence of adding JJRDF, JJRDF-CXHC, JJRDF-CXHPC, and JJRDF-CXHA at 3–5 g/100 g. Moreover, JJRDF-CXHC and JJRDF-CXHPC were better at improving the textural quality of the unmodified HA-EPG compared to JJRDF-CXHA and JJRDF (p < 0.05). Therefore, to improve egg protein gel quality, JJRDF modified with cellulase and xylanase hydrolysis separately coupled with carboxymethylation and crosslinking is a good choice. However, the functionalities of these modified JJRDFs should be studied.